Social Media as a Space for Islamophobia: COVID and Social-Environment Crisis Management - Chakraborty, Swati (Muslim Politics Review, 2023)
The COVID-19 pandemic has exposed an emergency of prejudice and savagery via social media by traditional ‘patriots’ in India. Meta, Twitter, and Instagram have turned into digital spaces full of deception about the pandemic. Hindu Instagram accounts such as @Hindu_secrets and @Hindu_he_hum have been unwavering and dedicated in spreading Islamophobic crusades by utilizing the COVID-19 pandemic. This has opened doors for hatred directed at Muslim people in India. This study situates itself inside the system of Stuart Hall's encoding and translating hypothesis to reveal the visual and printed codes used to make shameful and obtrusive generalizations that dehumanize and slander specific networks utilizing social media platforms. This is an explorative request that took part through a semiotic examination of the Instagram accounts of @Hindu_secrets and @Hindu_he_hum. The review tracked down encoded generalizations of danger in the utilization of variety, strict designs, garments, and other actual markers of social character in producing Islamophobic content. COVID-19 was depicted to as having Islamic parentage in the images; consequently, it depicted the Muslim people group as sustaining and deliberately spreading the infection across India and abroad.